Pathway to Public Health: Investigating Reasons Behind the University of Sunderland Students Pursuit of Postgraduate Studies - Oiboh , Stephanie Nehita; Sivasubramanian, Madhini (Queeva Publishing, 2024)
Background: Postgraduate studies in public health are vital for addressing global healthcare challenges. This study examines the factors motivating students at the University of Sunderland to pursue advanced degrees in public health, aiming to understand both personal and external influences on their educational choices. Methods: The study employed a cross-sectional quantitative design, utilizing a structured questionnaire with closed-ended questions. The research was conducted at the University of Sunderland's main and London campuses, targeting postgraduate public health students. Purposive sampling was used to select participants, and data were analyzed using SPSS version 28.0, focusing on descriptive statistics such as frequencies, percentages, and standard deviations. Results: Out of 102 respondents, 94 met the eligibility criteria. The mean age was 31.5 years, with a majority being female (61.8%) and from the African continent (58.5%). Most respondents (52.1%) had clinical experience, and a significant portion (66%) cited career advancement as their primary motivation. Other notable motivations included improving community health (60.6%) and a desire to work in healthcare policy (44.7%). Cultural background significantly influenced motivations related to global health challenges, while academic history significantly affected motivations concerning community health improvement and disease prevention. Discussion: The findings highlight the diverse motivations driving students to pursue postgraduate public health studies, with career advancement being the most significant factor. Cultural and academic backgrounds play crucial roles in shaping these motivations, suggesting the need for tailored support and resources to address the specific needs of diverse student populations. The study underscores the importance of understanding these motivational factors to enhance educational strategies and support services for public health students.